FEMALE GAMERS' EXPERIENCES IN THE VALORANT COMMUNITY: A PHENOMENOLOGICAL STUDY AND THE SOCIAL CONSTRUCTION OF TECHNOLOGY - Jalesita Putri Pramitha; Eni Maryani; Sri Seti Indriani (RADJA PUBLIKA, 2025)
This study explores the motives and meanings of female gamers in the women-only Valorant community, focusing on their experiences within the online gaming community. This phenomenon is relevant given the increasing participation of women in the male-dominated first-person shooter (FPS) game industry. Using Alfred Schutz's qualitative phenomenological approach and the Social Construction of Technology (SCoT) theory, this study aims to understand how female gamers' subjective experiences are shaped by social interactions and technological constructions within the community. Data were collected through in-depth interviews with purposively selected community members and then analyzed using thematic techniques. The results show that gaming motives encompass environmental influences and technological exploration, evolving into a need for entertainment, safe spaces, supportive social interactions, and self-actualization. Meanwhile, the meaning of the women-only community expands from its practical function as a place to play together to become a symbol of female empowerment and solidarity in a masculine digital space. These findings suggest that female gamer involvement is not only driven by recreational aspects but also related to identity formation, gender solidarity, and resistance to stereotypes. This research contributes to the study of the role of gender-based communities in creating an inclusive and equitable gaming ecosystem.